Realization of students' creative self-development technology (Pedagogy of Higher and Secondary Education, 2012)
Kokareva E. O. Realization of students' creative self-development technology.This article discusses the theoretical fundamentals of creative self-development of students and the results of its experimental testing in the educational process of higher education.
Keywords: heuristic learning; creative self-development; technology of creative self-development